O PROEJA ensino médio no ifrn, campus Caicó: causas da desistência e motivos da permanência - Faria, Débora Suzane de Araújo (2014)
This dissertation deals about the theme of National Integration Program of the Professional Education to the Basic Education in the form of Youth and Adults Education - PROEJA, which was developed at the Federal Institute of Education Science and Technology of Rio Grande do Norte - IFRN - Campus Caicó. It aims to analyze the causes of the abandonment and the reasons for the permanence of students within the mentioned program. To substantiate this research, we used methodologically, some procedures such as bibliographical research, documentary analysis, semi-structured interviews and focus group. To analyze the data, we discussed the contradiction that involves duality and educational compensation based in the struggles and achievements of rights at the core of public policies for high schools, for vocational education and the education of youth and adults in the 2000s. We analyze the integrated high school under PROEJA, having as reference the conception of the total human formation; the inseparability of the primary education system and vocational education and the integration of knowledge and expertise as a whole, discussing the specificities of the modality EJA, discussing the causes of abandonment and the reasons for the permanence of the students of education for youth and adults (EJA) in the primary education system. As for the results, we found that although the PROEJA be a program that aims to provide a complete human formation to contribute to the full citizenship of their graduate members, what is announced in the document that guides its creation has not been materialized in Caicó Campus. The curriculum of the course was not designed for the students of EJA, nor teachers have had an adequate training to work with these specific individuals, and its specificities of being workers with differentiated learning times have not been considered. In addition, the courses are predominantly of instrumentalist characteristics. This indicates that the material and institutional conditions to achieve the promised total and complete training have not being fully materialized at the researched school. Associated with the difficulties concerning the intra-school and extra-school conditions, personal and socioeconomic conditions which are related to the obligation to work that implies in limitations to balance work, school and family, they influenced in the interruption of the school trajectory of these subjects. Through research, we confirmed that the motives of students who remain have to do also with intraescolares conditions the quality of education (qualification of technical staff and teachers) involved in the educational process, as well as socioeconomic and personal issues represented by the support of colleagues and family.Then it is concluded that the causes of abandonment and the reasons of the permanence are of institutional, socioeconomic and personal origins. Finally, it is observed that capitalist society demands as much as possible high levels of educated workers, and at the same time makes difficult the access to that education for much of the population, and it is not randomly. The objects of that exclusion are the popular worker classes and their children